MAHAR PEMAHAMAN BESARAN MAHAR DALAM LITERATUR HADIS: STUDI TEMATIK DAN HISTORIS: PEMAHAMAN BESARAN MAHAR DALAM LITERATUR HADIS: STUDI TEMATIK DAN HISTORIS - Nurdiansyah, Enur; Wasman, Wasman; Rarawahyuni, Ika (El 'Ailaah, 2025)
Dowry is a form of protection from Allah SWT towards the purity of human nature, as well as recognition of gender equality in Islamic law. Giving a dowry is a form of a man's sincerity in building a household together with a woman, and is an acknowledgment of the wife's rights in owning and managing property, as the husband has those rights. This research aims to determine the provisions at dowry levels according to the hadith of the Prophet Muhammad SAW. The research method used is qualitative library research. The dowry in Islamic law is not the price paid by the husband in a sale and purchase transaction. It is more about glorifying a man to the woman he marries. Therefore, a man who wants to get married should prepare an appropriate dowry to honor his future wife, and a woman should not make things difficult for her future husband by asking for an excessive dowry. Islam does not strictly limit the amount of dowry. The price of the dowry, whether in the form of goods or services, is up to the agreement between the prospective husband and the prospective wife. When the dowry is not mentioned or has not been agreed upon at the time of the marriage ceremony, a mitsil dowry can be determined whose amount is equal to the general one in the community where the bride lives.